Crab-Eating Monkey Acidic Chitinase (CHIA) Efficiently Degrades Chitin and Chitosan under Acidic and High-Temperature Conditions - Uehara, Maiko; Takasaki, Chinatsu; Wakita, Satoshi; Sugahara, Yasusato; Tabata, Eri; Matoska, Vaclav; Bauer, Peter O; Oyama, Fumitaka (Molecules (Basel, Switzerland), 2022)
Chitooligosaccharides, the degradation products of chitin and chitosan, possess anti-bacterial, anti-tumor, and anti-inflammatory activities. The enzymatic production of chitooligosaccharides may increase the interest in their potential biomedical or agricultural usability in terms of the safety and simplicity of the manufacturing process. Crab-eating monkey acidic chitinase (CHIA) is an enzyme with robust activity in various environments. Here, we report the efficient degradation of chitin and chitosan by monkey CHIA under acidic and high-temperature conditions. Monkey CHIA hydrolyzed α-chitin at 50 °C, producing N-acetyl-d-glucosamine (GlcNAc) dimers more efficiently than at 37 °C. Moreover, the degradation rate increased with a longer incubation time (up to 72 h) without the inactivation of the enzyme. Five substrates (α-chitin, colloidal chitin, P-chitin, block-type, and random-type chitosan substrates) were exposed to monkey CHIS at pH 2.0 or pH 5.0 at 50 °C. P-chitin and random-type chitosan appeared to be the best sources of GlcNAc dimers and broad-scale chitooligosaccharides, respectively. In addition, the pattern of the products from the block-type chitosan was different between pH conditions (pH 2.0 and pH 5.0). Thus, monkey CHIA can degrade chitin and chitosan efficiently without inactivation under high-temperature or low pH conditions. Our results show that certain chitooligosaccharides are enriched by using different substrates under different conditions. Therefore, the reaction conditions can be adjusted to obtain desired oligomers. Crab-eating monkey CHIA can potentially become an efficient tool in producing chitooligosaccharide sets for agricultural and biomedical purposes.
Keywords: substrátová specifita; Chitin; koncentrace vodíkových iontů; vysoká teplota; oligosacharidy; chitinasy; Chitinases; FACE method; Chitosan; zvířata; Hydrogen-Ion Concentration; chitooligosaccharides; chitin; Oligosaccharides; Substrate Specificity; Hot Temperature; chitosan; Hydrolysis; hydrolýza; acidic chitinase; Animals